(untitled) (Papeles, 2021)
The article presents reflections emanating from the first stage of the participatory process for the construction of urban plans for the Rosario Metropolitan Area. This process sought to recover experiences, experiences and expectations of the citizens in order to achieve local plans, with a metropolitan perspective, that transcend the borders of the technical teams and managers of each locality. For this, the debates on the role played by local governments and the need to generate public policies with territorial actors are recovered. The notes presented here are intended to identify the potentialities and challenges of the process, as well as the tensions that emerged between the metropolitan and local visions. It tries to account for the impact of proximity and closeness on institutionalized citizen participation for the construction of public policies. For this, the participatory dimension is analyzed, recovering the characterization of the actors, the construction of the socio-urban question in the framework of the tension between the local and the metropolitan, and the notion of proximity in the framework of participatory processes. The analysis was complemented by conducting interviews with different actors from the different localities.